Measuring Service Quality: A Reexamination and Extension - Cronin, J. Joseph; Taylor, Steven A. (Journal of Marketing, 1992)
The authors investigate the conceptualization and measurement of service quality and the relationships between service quality, consumer satisfaction, and purchase intentions. A literature review suggests that the current operationalization of service quality confounds satisfaction and attitude. Hence, the authors test (1) an alternative method of operationalizing perceived service quality and (2) the significance of the relationships between service quality, consumer satisfaction, and purchase intentions. The results suggest that (1) a performance-based measure of service quality may be an improved means of measuring the service quality construct, (2) service quality is an antecedent of consumer satisfaction, (3) consumer satisfaction has a significant effect on purchase intentions, and (4) service quality has less effect on purchase intentions than does consumer satisfaction. Implications for managers and future research are discussed.